2012
DOI: 10.2169/internalmedicine.51.6858
|View full text |Cite
|
Sign up to set email alerts
|

Familial Behçet's Disease of Adult Age: A Report of 4 Cases from a Behçet Family

Abstract: A familial aggregation of Behçet's disease (BD) has long been noted. These studies have supported the direct role of HLA-B5 in the pathogenesis of BD. Despite the fact that familial clustering is characterized by genetic anticipation, accounting for the earlier disease onset in successive generations, we present two brothers and two cousins from the same family who were diagnosed when they were over twenty years old.We report these young adult patients to introduce the characteristics of familial aggregation o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(4 citation statements)
references
References 9 publications
0
4
0
Order By: Relevance
“…Immune fluorescence studies revealed IgM, IgG and β1 globulin on the vascular endothelial walls and the serum contained increased amounts of IgD, IgG, IgM, C1, C2, C3, C4 and immune complexes. The increased prevalence of the HLA-B5 tissue gene group suggests a genetic role as aetiological factor 13-15…”
Section: Discussionmentioning
confidence: 99%
“…Immune fluorescence studies revealed IgM, IgG and β1 globulin on the vascular endothelial walls and the serum contained increased amounts of IgD, IgG, IgM, C1, C2, C3, C4 and immune complexes. The increased prevalence of the HLA-B5 tissue gene group suggests a genetic role as aetiological factor 13-15…”
Section: Discussionmentioning
confidence: 99%
“…Erythema-Nodosum-like Lesions Neutrophilic infiltrates, panniculitis, and fat necrosis [8]. Studies described such infiltrates as a differential factor from Erythema Nodosum.…”
Section: Genital Ulcerationmentioning
confidence: 99%
“…Although most cases are sporadic, which makes diagnosing and predicting them a lot more complex, familial clusters are reported [7]. Furthermore, in these cases, genetic anticipation has been observed [8]. The global prevalence 2017 reached 14.6 per 100,000, with even higher prevalence rates along the Silk Route, like Turkey, with 420 per 100,000 [9,2].…”
Section: Introductionmentioning
confidence: 99%
“…Although BD has traditionally been considered sporadic there have been cases of familial clustering, suggesting a potential genetic predisposition to disease [14, 15]. Genetic anticipation, where the disease presents earlier in subsequent generations, is also evident [16]. …”
Section: Introductionmentioning
confidence: 99%